Hydrochemical characterization and sustainability assessment of Ismailia canal water, Eastern Nile Delta, Egypt: implications for human health and environmental safety - El-Said Salem, Zenhom; Attiah, Abdullah Muhammad; Abu-Alam, Tamer (Frontiers in Environmental Science, 2024)
Surface freshwater systems globally face severe stresses due to overpopulation and associated waste. The Ismailia Canal, a crucial freshwater source in the eastern Nile Delta, Egypt, serves multiple purposes and is endangered by various environmental activities. This study characterizes the canal’s water using physicochemical parameters to evaluate its suitability for different uses. Water samples were collected twice in winter and summer seasons of the year 2018 from eight sites distributed along the course of Ismailia Canal. A comprehensive chemical analysis of the samples was carried out. Water chemistry was graphically and statistically assessed. Water qualities were evaluated using WHO guidelines, water quality index (WQI), Pollution indices of metals (PIm) and long- and short-term effect of trace elements on irrigation. Results show that the water is slightly alkaline and moderately hard, with higher salinity in winter than summer. Major cations and anions are higher in winter, whereas NO₃ is higher in summer. The canal water is primarily of the Ca(Mg)-HCO₃ type, influenced mainly by rock-water interactions. While most physicochemical parameters meet drinking water standards, Al, Sb, As, Cd, Fe, Pb, and Tl exceed limits, with significant impacts from Al and Tl year-round, and seasonal impacts from As, Pb, Cd, and Fe. For irrigation, water quality is generally unaffected in winter, but Mo and Se have slight impacts in summer for long-term use. This research is vital for informing sustainable water management practices, which are crucial for Egypt’s research initiatives, economic stability, and environmental sustainability.